Sabar dan Flourishing pada Ibu-ibu Pengajian - Annisa Eka Putri; Ahmad Hidayat (Psychopolytan : Jurnal Psikologi, 2024)
Flourishing is one of the concepts studied in positive psychology. One of the factors that contributes on flourishing is patience. This research aims to determine the effect of patience on flourishing to mothers who take a part in recitation. The sample was 125 recitation mothers with an average age of 41-50 years old with using snowball sampling technique. This research used Schnitker's (2012) 3-FPQ (Three-Factor Patience Questionnaire) scale with 11 items and Effendy and Subandriyo's (2017) flourishing scale with 23 items. The data analysis technique used is Partial Least Square (PLS) with smartPLS 3.0 software. The results of the analysis show that patience has a positive and significant effect on flourishing with a p value <0.05. The contribution of the influence of the patience variable is able to explain the flourishing variable by 9.9%. Recommendations for future researchers are expected to examine other factors that are assumed to have a greater effect on flourishing, expand research subjects and use qualitative methods to gain a deeper understanding. These findings strengthen other research that show how patience affects flourishing.